Design and implementation of a reconfigurable mixed-signal SoC based on field programmable analog arrays *Project supported by the National High Technology and Development Program of China (No. 2012AA012303). (November 2017) - Liu, Lintao; Gao, Yuhan; Deng, Jun
Abstract: This work presents a reconfigurable mixed-signal system-on-chip (SoC), which integrates switched-capacitor-based field programmable analog arrays (FPAA), analog-to-digital converter (ADC), digital-to-analog converter, digital down converter, digital up converter, 32-bit reduced instruction-set computer central processing unit (CPU) and other digital IPs on a single chip with 0.18 μ m CMOS technology. The FPAA intellectual property could be reconfigured as different function circuits, such as gain amplifier, divider, sine generator, and so on. This single-chip integrated mixed-signal system is a complete modern signal processing system, occupying a die area of 7 × 8 mm 2 and consuming 719 mW with a clock frequency of 150 MHz for CPU and 200 MHz for ADC/DAC. This SoC chip can help customers to shorten design cycles, save board area, reduce the system power consumption and depress the system integration risk, which would afford a big prospect of application for wireless communication.